2021
DOI: 10.3389/fphys.2021.731234
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Angiopathy of Lacrimal Gland Lesion in Type 2 Diabetes

Abstract: For a better understanding of diabetic angiopathy (DA), the potential biomarkers in lacrimal DA and its potential mechanism, we evaluated the morphological and hemodynamic alterations of lacrimal glands (LGs) in patients with type 2 diabetes and healthy counterparts by color Doppler flow imaging (CDFI). We further established a type 2 diabetic mice model and performed hematoxylin-eosin (HE) staining, immunofluorescence staining of CD31, RNA-sequencing analysis, and connectivity map (CMap) analysis. We found at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Our results support previous studies showcasing atrophied acini in the diabetic lacrimal gland that may reflect decreased cell size and/or secretory function [ 24 , 31 ]. Studies have shown that diabetic rats have smaller secretory vesicles, decreased levels of cations, and decreased total protein [ 24 , 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our results support previous studies showcasing atrophied acini in the diabetic lacrimal gland that may reflect decreased cell size and/or secretory function [ 24 , 31 ]. Studies have shown that diabetic rats have smaller secretory vesicles, decreased levels of cations, and decreased total protein [ 24 , 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, excessive or chronic inflammation can damage ocular surface tissues and decrease tear film stability, e.g. corneal epithelial defects, decreased corneal nerves [3] decreased conjunctival cuprocytes [4], and atrophy of lacrimal gland alveoli [5]. Numerous prospective and retrospective cohort studies have highlighted the relationship between pro-inflammatory cytokines (e.g., IL-1β, TNF-α, IL-6, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…T2DM DE is closely related to inflammation [2]. Inflammation on the ocular surface of DE patients with T2DM will lead to destruction of corneal epithelial barrier, nerve damage [3], apoptosis of conjunctival goblet cells [4], and atrophy of lacrimal gland acinifphys [5] causing discomfort symptoms such as dryness, burning sensation, foreign body sensation in the patient's eyes, and even leading to visual dysfunction [6], seriously affecting the life quality of patients..Currently, the eye drops commonly used clinically for T2DM DE include artificial tears and steroid drops [7]. Artificial tears do not have a direct anti-inflammatory effect, treating the symptoms but not the root cause; steroid hormone eye drops will produce increased intraocular pressure, cataracts and other adverse reactions after long-term use [8].Therefore, effective and safe treatment strategies need to be explored for T2DM…”
Section: Introductionmentioning
confidence: 99%
“… 22 The Molecular Complex Detection (MCODE) plugin in Cytoscape was then used to cluster the protein interactions in the network using a node score cutoff of 0.2, a module score of >4, a degree cutoff of 2 and a maximum depth of 100. 23 , 24 , 25 , 26 , 27 Next, the Cytohubba plug-in in Cytoscape was used to identify biologically important hub genes that are highly connected via protein-protein interactions as documented in the supplementary text. 28 , 29 …”
Section: Methodsmentioning
confidence: 99%